2022
DOI: 10.3389/fpls.2021.807710
|View full text |Cite
|
Sign up to set email alerts
|

Plant Responses Underlying Timely Specialized Metabolites Induction of Brassica Crops

Abstract: A large subset of plant stress-signaling pathways, including those related with chemical defense production, exhibit diurnal or circadian oscillations. However the extent to which diurnal or circadian time influences the stress mediated accumulation of plant specialized metabolites remains largely unknown. Because plant responses to physical stress (e.g., wounding) is considered a common component of mounting a response against a broad range of environmental stresses, including herbivory, we have utilized mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…As expected, the most induced compounds after wounding were indole GSLs, but with high variation in timing of injury among genotypes. Previous studies have also shown that induction of specialized metabolites after wounding or herbivory varies across species and genotypes in terms of their circadian or diurnal response (Arimura et al 2008;Kim et al 2011;Baldwin & Meldau 2013;Doghri et al 2022). Notably, several aliphatic GSL and phenolic compounds were lower after morning and evening wounding than in controls, while midday treatment induced several such compounds (Fig.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…As expected, the most induced compounds after wounding were indole GSLs, but with high variation in timing of injury among genotypes. Previous studies have also shown that induction of specialized metabolites after wounding or herbivory varies across species and genotypes in terms of their circadian or diurnal response (Arimura et al 2008;Kim et al 2011;Baldwin & Meldau 2013;Doghri et al 2022). Notably, several aliphatic GSL and phenolic compounds were lower after morning and evening wounding than in controls, while midday treatment induced several such compounds (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…Consistent with such oscillations, specialized metabolites that mediate plant defence are synchronized with Lepidoptera, aphid and pathogen circadian behaviour in Arabidopsis thaliana and related Brassica crops (Goodspeed et al 2012(Goodspeed et al , 2013Lei et al 2019;Rupp et al 2020). More recently, Doghri et al (2022) revealed that induction of glucosinolates (GSL), major plant defence metabolites in the Brassicaceae, depends on the time during the day at which the stress event (attack) takes place. However, the internal reshaping of plant growth under daily stress sensing, the circadian and photoperiodic gating of plant responses, and their metabolic coordination remain to be investigated.…”
Section: Introductionmentioning
confidence: 87%
“…Temperature records from the Veenkampen 3 , Wageningen, The Netherlands, weather station indicate daily maximal and minimal temperatures fluctuating between 11-33 ℃ and 0.1-20.5℃, respectively, with an average daily temperature variation (i.e., maximal -minimal temperature) of 11.6 ℃. Although the effects of thermal variation were not analysed in this dataset, effects of temperature and herbivore species diversity on plant phytochemical profiles have been reported in other studies, suggesting that both factors are likely to interact to mediate community dynamics (Doghri et al, 2021;Kask et al, 2016;Mikkelsen et al, 2015;Truong et al, 2014). Ecosystems dynamics are marked by seasonality and the composition of the previous species assemblage influences the composition of the subsequent assemblage (Heinen et al, 2022;Stam et al, 2019).…”
Section: The Role Of Community Context In Species Responses To Extrem...mentioning
confidence: 81%
“…Plant phytochemistry fluctuates over time (e.g. year, season, day), allowing plants to optimise their metabolic activity to match their environmental conditions (Doghri et al, 2021;Gols et al, 2007). Mechanical wounding of Lima bean (Phaseolus lunatus L.; Fabaceae) leaves as a mimic of herbivore damage during the photo-or scotophase resulted in differential emission of herbivore induced plant volatiles (HIPVs) (Arimura et al, 2008).…”
Section: Consequences For Trophic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation